WATER QUALITY AT THE LAGOONS FROM BINH DINH TO NINH THUAN PROVINCES IN RECENT TIME - Vinh, Le Thi (Vietnam Journal of Marine Science and Technology, 2015)
The research results of water quality in the lagoons from Binh Dinh to Ninh Thuan (De Gi, Thi Nai, O Loan, Nha Phu, Thuy Trieu, Nai) during 2007-2011 showed that the values of the basic parameters (Salinity: 0 - 34‰, TSS: 4.3 mg/l to 150 mg/l, pH: 6.75 to 8.3, DO: 3.99 mg/l to 8.09 mg/l, BOD5: 0.38 - 6.29 mg/l), nutrients (Ammonia: 0 - 168 μgN/l, nitrite: 0 -        51 μgN/l, nitrate: 28 - 493 μgN/l, silicate: 83 - 6040 μgSi/l), organic matters (N: 298 - 1660 μg/l, P: 12.9 μg/l to 691.9 μg/l), Fe (65 - 1850 μg/l) and coliform density (0 - 46000 MPN/100 ml) changed in a very wide range, especially in the rainy season while the values of the heavy metals (Zn: 4.7 - 23.6 μg/l , Cu: 0.5 - 5.5 μg/l, Pb: 0.1 - 4.3 μg/l) and hydrocarbon (233 - 833 μg/l) varied in the narrower range. In general, water quality in the lagoons of De Gi, Thi Nai, Nha Phu, Thuy Trieu and Nai in the dry season was better than that in the wet season while water quality in the O Loan lagoon had an opposite trend because An Hai inlet opening in this lagoon occurred in the rainy season. In the lagoons, especially Thi Nai, O Loan, Nai and Nha Phu, values of DO, TSS, ammonia, nitrate, phosphate, Fe, HC and coliform were not in the range of critical values for aquaculture and aquatic conservation, particularly during the rainy season in the top of lagoons and the river mouths discharging into the lagoon. However, environmental concerns were mainly DO, nutrient levels (especially phosphate) and coliform density.